(untitled) (Al-Qamar, 2020)
Ṣaḥīḥ Muslim, a well-known collection of Prophetic traditions, is considered to be a second most legitimate ḥadīth corpus after Ṣaḥīḥ al-Bukhārī. Number of translations and commentaries of this book have been written. Fatḥ al-Mulhim by Shabbīr Ahmad Usmānī and Minnat ul-Muʻim by Ṣafī-ur-Raḥmān Mubārakpūrī are two prominent Arabic commentaries written in Indo-Pak subcontinent. This article studies the methodologies of these two commentaries. It finds that along with number of commonalities, both the commentators have mentionable differences in elaborating the ḥadīths and developing the arguments in support of their opinions regarding the explanations of different ḥadīths and related words, phrases and personalities etc. Both offer arguments from Quran, ḥadīth, Arabic grammar and previous scholars etc. but Usmānī goes into more details of the relevant issues than Mubārakpūrī.